ADVANCED FOREIGN EXPERIENCES IN IMPROVING THE EFFICIENCY OF HOUSING FUND MANAGEMENT - Professor., Toshboyev Abduraim Jabbarovich; Dosent., Bustonov Komiljon Kumakovich; Mirzayev Musurmon Umidullaevich; Normurodov Sarvar Norboy ugli (Scholar Express Journals, 2023)
In this article, introduction of quality management to the housing fund, management of the housing fund, improvement of the efficiency of the housing fund, advanced foreign experiences of the housing fund are covered
Keywords: housing fund; introduction of quality management to housing fund; housing fundadvanced foreign experiences.